Experimental investigation of flow and heat transfer in a channel with dimpled plate (2019)
This study presents the experimental investigation on the effect of dimpled arrangements on flow and heat transfer characteristics. Three plate surfaces were prepared (smooth, evenly distributed spherical dimples and unevenly distributed spherical dimples) and were placed successively in a channel. The unevenly distributed dimpled plate had the same dimple density with the evenly distributed dimpled plate but had varying transverse pitches to concentrate the dimples at midplate in flow direction. Data obtained from the experiment were analysed to determine the performance of each dimpled plate channel. It was observed that the average Nusselt number due to the heat interaction with the air-flow increases with the Reynolds number. The evenly and unevenly dimple plate channels had respectively, 75.7% and 91.8% increase in Nusselt number over the smooth channel. The flow friction factors of the evenly and unevenly dimple plate channels were merely more than that of smooth plate channel by 0.59% and 0.67%, respectively. Thus, the unevenly dimple plate channel had the highest overall thermal-hydraulic performance, followed by the evenly dimple plate channel.